Funde aus Milet XXII. Etruscan Bucchero from Miletus: Preliminary Report - Naso, Alessandro (Archäologischer Anzeiger, 2014)
Bucchero, the Etruscan national pottery, was appreciated also by Greeks, who adopted in their culture the form of the commonest Etruscan vase, the kantharos, as an attribute of Dionysos.This adoption led to a widespread distribution of this vase in the Greek world, which is also clearly demonstrated by the bucchero finds in the Aegean. Here Miletus is the richest bucchero findplace, since the excavations conducted by V. von Graeve from 1985 onwards have produced more than 100 Etruscan bucchero sherds, belonging mostly to kantharoi, which were dedicated in the Aphrodite sanctuary. Mineralogical and petrographical analysis carried out by G.Trojsi has enabled us to identify the probable Etruscan production centres of the bucchero pots by comparison with the results of previous research.These centres are Caere and Tarquinia, two of the most important Etruscan city-states, which had direct relationships with Miletus.